PENGARUH PERBANDINGAN ARANG LIMBAH PELEPAH KELAPA SAWIT DAN KULIT KAKAO TERHADAP MUTU BRIKET ARANG DI DESA TIMBANG JAYA KECAMATAN BAHOROK, KABUPATEN LANGKAT, PROVINSI SUMATERA UTARA - Muhammad Taufiq (Universitas Pembangunan Panca Budi, 2019)
This study aims to analyze the right combination of charcoal briquette between charcoal from palm stem andcharcoal from cocoa fruit shell waste so that the charcoal briquette results that are appropriate or close to SNI quality standards. Data analysis method in this study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications in each treatment. Comparison between palm stem charcoal and cocoa fruit shell charcoal added with starch adhesive as much as 5% respectively 70%: 30% (P1), 60%: 40% (P2), 50%: 50% (P3) , 40%: 60% (P4) and 30%: 70% (P5). Testing samples in this study include heating value/ calorific value, moisture content, power and combustion efficiency. The result showed that the water content which was found from all the five treatments given had higher water content compared to SNI. The maximum water content of the charcoal briquettes that conforms to SNI is < 8%, so there is no charcoal briquette treatment that matches to SNI criteria. The heat value contained in the charcoal briquettes is greater than the SNI which is > 5000 Kal/ g, so all the five treatments of charcoal briquettes have fulfilled the SNI. While the value of power and efficiency of combustion has not yet been stated in SNI, the power and efficiency of combustion only refers to the lowest average value or briquettes with combustion efficiency that has the longest combustion time used as the best power and efficiency of combustion, so the best quality standard of combustion efficiency is the combination of charcoal briquettes from 70% palm stem and 30% cocoa fruit shell (P1) because it refers to the combustion efficiency of briquettes that have the longest combustion time.